2006
DOI: 10.1111/j.1745-7254.2006.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

PPAR gamma inhibits growth of rat hepatic stellate cells and TGF beta-induced connective tissue growth factor expression1

Abstract: Aim: To investigate the effect of peroxisome proliferator-activated receptor gamma (PPARγ ) activation on the growth of rat hepatic stellate cells (HSC) and transforming growth factor beta (TGF-β)-induced connective tissue growth factor (CTGF) expression. Methods: After being treated with various amounts of the PPARγ natural ligand 15-deoxy-∆12,14-prostaglandin J 2 (15-d-PGJ 2 ) or synthetic ligand GW7845, the status of HSC proliferation and apoptosis were detected by MTT assay and flow cytometry. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 34 publications
2
60
0
Order By: Relevance
“…According to these authors, GW7845 may prevent adipocytic HSCs by acquiring a myofibroblastic phenotype during chronic liver injury [183]. These results were confirmed in another in vitro study on HSCs rat in which GW7845 inhibited the growth of HSCs and TGF 1-induced CTGF expression, thus confirming itself as a potential antifibrotic compound in treating and preventing liver fibrosis [247].…”
Section: Ppar Agonistssupporting
confidence: 72%
“…According to these authors, GW7845 may prevent adipocytic HSCs by acquiring a myofibroblastic phenotype during chronic liver injury [183]. These results were confirmed in another in vitro study on HSCs rat in which GW7845 inhibited the growth of HSCs and TGF 1-induced CTGF expression, thus confirming itself as a potential antifibrotic compound in treating and preventing liver fibrosis [247].…”
Section: Ppar Agonistssupporting
confidence: 72%
“…PPARγ ligands also inhibit expression of TGFβ1-regulated genes, such as connective tissue growth factor (CTGF) in activated, myofibroblastic HSC (19). However, the mechanisms involved may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CTGF in HSCs is up-regulated by numerous profibrotic factors, including TGF-␤ (4,18,19), endothelin-1 (20), PDGF-BB, acetaldehyde (21), ethanol (22), and the Th2 cytokine IL-13 (23,24), with TGF-␤ being the most important trigger as elevated TGF-␤ levels are observed in almost all fibrotic liver diseases, irrespective of etiology. Although in vitro experiments have shown that TGF-␤ plays only a minor role in CTGF production in quiescent HSCs (20,23,24), activated HSCs as well as established HSC cell lines secrete high levels of CTGF in response to TGF-␤ treatment (22,23).…”
Section: Connective Tissue Growth Factor (Ctgf)mentioning
confidence: 99%